2008
DOI: 10.1371/journal.pntd.0000271
|View full text |Cite
|
Sign up to set email alerts
|

Landscape Diversity Related to Buruli Ulcer Disease in Côte d'Ivoire

Abstract: BackgroundBuruli ulcer disease (BU), due to the bacteria Mycobacterium ulcerans, represents an important and emerging public health problem, especially in many African countries. Few elements are known nowadays about the routes of transmission of this environmental bacterium to the human population.Methodology/Principal FindingsIn this study, we have investigated the relationships between the incidence of BU in Côte d'Ivoire, western Africa, and a group of environmental variables. These environmental variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
71
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(78 citation statements)
references
References 24 publications
6
71
0
1
Order By: Relevance
“…7,9,30 However, studies on the relationship between landscape diversity and BU disease are still rare. Brou and others 8 reported that landscape diversity was related to BU in Cote d'Ivoire. They found that the BU risk zones were located at irrigated rice field cultures areas, banana fields, and areas close to dams used for irrigation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…7,9,30 However, studies on the relationship between landscape diversity and BU disease are still rare. Brou and others 8 reported that landscape diversity was related to BU in Cote d'Ivoire. They found that the BU risk zones were located at irrigated rice field cultures areas, banana fields, and areas close to dams used for irrigation.…”
Section: Discussionmentioning
confidence: 98%
“…6 These studies highlight an increased understanding of landscape patterns and disease risk, but to date few studies have evaluated the usefulness of pattern metrics on Buruli ulcer (BU) prevalence, 7 despite the fact the changes in land use have been previously reported in association with the disease. [8][9][10] Understanding how landscape patterns influence human disease could aid the development of landscape-level management plans to reduce disease risk.…”
Section: Introductionmentioning
confidence: 99%
“…Exploitation of natural resources or improvement in infrastructure is necessary for economic growth in tropical countries, but this often comes at the expense of rapid environmental change that can increase the prevalence of local infectious diseases [46]. For instance, changes in agricultural practices, deforestation and the construction of roads and dams have contributed to the emergence of BU endemic areas [18][19][20]. Given the potential that some NTDs have to drag part of the population into poverty, the negative consequences of environmental degradation could fall disproportionally on few individuals, while most of the population enjoys the economic benefits.…”
Section: Discussionmentioning
confidence: 99%
“…L'Afrique occidentale semble véritablement touchée par cette maladie depuis deux décennies, avec une recrudescence inquiétante au cours de la présente décennie, malgré sa très faible contagiosité . La Côte d'Ivoire, est un pays endémique à cette pathologie (Brou et al, 2008 ;Fener, 2015). Cette infection occupe le deuxième rang des mycobactériose en Côte d'ivoire après la tuberculose et avant la lèpre .…”
Section: Introductionunclassified